The monster sound pipe. (19th January 2017) - Ruiz, Michael J; Perkins, James
Abstract: Producing a deep bass tone by striking a large 3 m (10 ft) flexible corrugated drainage pipe immediately grabs student attention. The fundamental pitch of the corrugated tube is found to be a semitone lower than a non-corrugated smooth pipe of the same length. A video (https://youtu.be/FU7a9d7N60Y ) of the demonstration is included, which illustrates how an Internet keyboard can be used to estimate the fundamental pitches of each pipe. Since both pipes have similar end corrections, the pitch discrepancy between the smooth pipe and drainage tube is due to the corrugations, which lower the speed of sound inside the flexible tube, dropping its pitch a semitone.